Reaktivasi Bank Sampah Dan Pemberdayaan Masyarakat Di Kelurahan Ngroto Oleh Mahasiswa Kuliah Kerja Nyata (KKN) UNS - Yudi Rinanto; Gamya Abi Putra Irawadi; Akhsa Felia Primandajat; Nuzula Dionessa Nurhaji; Riones Salomo; Aisyah Nur Inayah; Laras Adi Kinasih; Bunga Seftya Beltiartono; Salsabila Putri Fardiani; Dewi Fatimatuzzahro; Azzahra Aprilian Aufa (Universitas Sebelas Maret, 2025)
Waste bank is a system that operates in the field of waste management. Waste banks are a business model that was established in Indonesia in 2008. Waste banks can be used to accommodate and educate the public regarding waste management. Waste bank systems and mechanisms need to be improved or modified to increase waste acceptance from the community. Waste is a problem in almost all regions in Indonesia. Waste bank management can produce derivative products. Waste bank derivative products that have been successfully produced are organic fertilizer and paving blocks mixed with plastic. Managing waste into derivative products has the potential to create employment opportunities and empower communities